Endocytosis of keratinocytes in oral squamous cell carcinoma: Expression of phagocytic markers. (9th December 2015) - Sarode, Sachin C; Sarode, Gargi S; Kulkarni, Meena; Patil, Shankargouda
Objectives: To quantify endocytosis of keratinocytes (EK) in oral squamous cell carcinoma (OSCC) and correlate it with different clinical and histopathological parameters. Further, the expression of cluster of differentiation 68 (CD68) and lysozyme was studied in tumor cells to corroborate this phenomenon. Materials and method: EK per high-power field (HPF) was calculated on hematoxylin and eosin-stained sections and correlated with clinical and histopathological parameters. CD68 and lysozyme were studied in tumor cells using immunohistochemistry. Results: The mean EK per HPF was higher in stage IV (4.450 ± 2.241) than stage III (3.333 ± 1.543) OSCC ( p = 0.1978). Although there were more EK in N2 stage (4.362 ± 0.3405) as compared to N0–N1 (3.462 ± 0.4178), the results were statistically insignificant. Statistically significant difference in mean EK was observed in all the grades of OSCC: well versus moderate ( p = 0.0052), moderate versus poor ( p < 0.0001), and well versus poor ( p = 0.0001). There were significant differences in the mean EK ( p < 0.05) between different grades of stromal degenerations (mild: 2.654 ± 1.093, moderate: 5.115 ± 1.774, and severe: 7.250 ± 2.217). Statistically significant differences were observed in CD68 expression in tumor cells of various TNM stages ( p = 0.049), histopathological grades ( p = 0.045), and stromal degeneration ( p = 0.024). Likewise, lysozyme expression in tumor cells was also statistically significant in histopathological grades ( p = 0.004) and mean EK value ( p = 0.0119). Conclusion: The mean EK in OSCC increases with increasing histopathological grades, TNM stages, and stromal degeneration. CD68 and lysozyme can be used as markers of EK in OSCC.